(Re)making labour markets and economic crises: The case of Ireland. (March 2019) - Murphy, Enda; Mercille, Julien
The 2008 economic crisis has had significant impacts on labour markets around the world. In Europe, in particular, the need for internal devaluation within European Union nations in financial difficulty precipitated a wave of labour market reforms alongside the reform of welfare systems struggling to cope with high levels of unemployment. Various analyses have explored the nature of these changes separately for the labour market and welfare systems. Using a conceptual framework rooted in a political economy understanding the social nature of labour, this article takes an inclusive approach to understanding regulatory changes for both employed and unemployed labour. We do this using the case of Ireland, a country that went through a severe economic crisis, was subject to a European Union/European Central Bank/International Monetary Fund bailout in 2010 and witnessed one of the most significant labour market crises in Europe. The Irish case is instructive because it highlights both the range and depth of regulatory interventions utilised by the state during periods of crisis to deal with the social nature of labour and its role under advanced capitalism. JEL codes: J01, J08, J48.